PENEGAKAN HUKUM ADMINISTRASI LINGKUNGAN HIDUP DITINJAU DARI KONSEP NEGARA HUKUM - Atika Thahira (JCH (Jurnal Cendekia Hukum), 2020)
Indonesia, Indonesia is a nation of law that uses a rule of law country (rechtstaat) concept. The concept of rule of law Indonesia set forth in its Constitution, the 1945 Constitution, Article 1 paragraph (3). There is an important element of democracy stated on the Constitution, namely the protection of human rights, that every citizen has the right to enjoy it. One of the rights protected in the Constitution is right to access a good and healthy living environment. For this, the environment needs to be preserved and function through administrative law enforcement. The study uses normative juridical approach with descriptive-analytics, which describes the norms and associated with theories, and opinions of legal experts. The development of a democratic nations of law can be seen from the aspect of law enforcement in particular with environmental administration. In Indonesia, it can be reviewed through the theory of organic states and the theory of pluralist states. Based on the theory of an organic state and looking at the aspects of environmental administration law enforcement in Indonesia, the state has regulated the enforcement of environmental administrative sanctions whereby the state can regulate every activity and/or business in the environmental issues. Therefore, the pluralist state theory recognized a variety of diverse interests  in society that the state has accommodated all citizens rights to a good and healthy environment through pro-environment government policies.